2013
DOI: 10.1093/epirev/mxt012
|View full text |Cite
|
Sign up to set email alerts
|

Negative Spinal Bone Mineral Density Changes and Subclinical Ovulatory Disturbances—Prospective Data in Healthy Premenopausal Women With Regular Menstrual Cycles

Abstract: Subclinical ovulatory disturbances (anovulation or short luteal phases within normal-length menstrual cycles) indicate lower progesterone-to-estrogen levels. Given that progesterone plays a bone formation role, subclinical ovulatory disturbances may be associated with bone loss or less than expected bone gain. Our purpose was to perform a meta-analysis of prospective studies in healthy premenopausal women to determine the overall relationship of subclinical ovulatory disturbances to change in bone mineral dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 68 publications
1
44
0
1
Order By: Relevance
“…Thus, no apparent or physical indication of a menstrual disturbance occurred, and subtle menstrual disturbances were detected exclusively by the measurement of urinary metabolites of menstrual cycle hormones. Consequently, exercising women may be experiencing subtle forms of menstrual dysfunction secondary to an energy deficit but may not be aware of such disturbances or the potential impact of these disturbances on fertility and bone health (13,18,24).…”
Section: E36 Energy Deficit Predicts Frequency Of Menstrual Disturbancesmentioning
confidence: 99%
“…Thus, no apparent or physical indication of a menstrual disturbance occurred, and subtle menstrual disturbances were detected exclusively by the measurement of urinary metabolites of menstrual cycle hormones. Consequently, exercising women may be experiencing subtle forms of menstrual dysfunction secondary to an energy deficit but may not be aware of such disturbances or the potential impact of these disturbances on fertility and bone health (13,18,24).…”
Section: E36 Energy Deficit Predicts Frequency Of Menstrual Disturbancesmentioning
confidence: 99%
“…Oestrogen increases uptake of calcium into blood and deposition into bone, while progesterone facilitates the actions of oestrogen through multiple complex mechanisms 34. Even silent oestrogen/progesterone imbalance, as seen in subclinical ovulatory disturbances with low EA may produce negative changes in bone 35. In men and women, testosterone has anabolic effects on bone, stimulating osteoclasts and increasing bone formation and calcium absorption 36.…”
Section: Introductionmentioning
confidence: 99%
“…Several parameters were not evaluated, such as bone metabolism markers, sex hormones (e.g., estrogen and progesterone), and reproductive maturation (such as tanner breast stage). Moreover, a previous study reported that subclinical ovulatory disturbance provides negative effect on bone [29]; however, the present study did not assess that. Low-dose oral contraceptives may impair the attainment of peak bone mass [30].…”
Section: Discussionmentioning
confidence: 72%